Inside Back Cover: Volume 1 Issue 1. Issue 1 (31st January 2022) - Unknown
Abstract : Inside Back Cover : The crystal structure of cubic TiP2 O7 in center shows the research object and displays its three‐dimensional ion channels. The moving particles and electric current represent magnesium‐ion diffusion and electronic transports, showing the reaction of TiP2 O7 in magnesium‐ion batteries. Green background means "Green Earth". The electric vehicle, wind turbines, solar cell and energy storage station emphasize the potential application fields of magnesium‐ion batteries. The word "Mgood" in energy storage station means "Material is good" and "Mg is good".